Expression of a stress-inducible heme oxygenase-1 in NK cells is maintained in the process of human aging - Kaszubowska, Lucyna; Kaczor, Jan Jacek; Karnia, Mateusz Jakub; Foerster, Jerzy; Kmieć, Zbigniew (Frontiers in Immunology, 2024)
Introduction: Heme oxygenase-1 (HO-1) is a stress-inducible heat shock protein (HSP32) that exerts cytoprotective effects against oxidative stress and inflammation, and is involved in the maintenance of cellular homeostasis. This study aimed to evaluate the expression of HO-1 in natural killer (NK) cells from individuals of different age groups after stimulation with various factors, and to analyze the relationships between the concentration of this cytoprotective protein and parameters corresponding to oxidative stress and inflammation, that is, NOD-like receptor protein 3 (NLRP3), glutathione (GSH), GSH disulfide (GSSG), and interleukin 6 (IL-6). Methods: The study population comprised three age groups: young adults (age range, 19–23 years), older adults aged under 85 years (age range, 73–84 years), and older adults aged over 85 years (age range, 85–92 years). NLRP3, GSH, and GSSG concentrations were measured in serum, whereas the HO-1 concentration and IL-6 expression were studied in NK cells cultivated for 48 h and stimulated with IL-2, lipopolysaccharide (LPS), or phorbol 12-myristate 13-acetate (PMA) with ionomycin. Results: The analysis of serum NLRP3, GSH, and GSSG concentrations revealed no statistically significant differences among the studied age groups. However, some typical trends of aging were observed, such as a decrease in GSH concentration and an increase in both GSSG level, and GSSG/GSH ratio. The highest basal expression of IL-6 and lowest basal content of HO-1 were found in NK cells of adults over 85 years of age. The NK cells in this age group also showed the highest sensitivity to stimulation with the applied factors. Moreover, statistically significant negative correlations were observed between HO-1 and IL-6 expression levels in the studied NK cells. Conclusions: These results showed that NK cells can express HO-1 at a basal level, which was significantly increased in activated cells, even in the oldest group of adults. The reciprocal relationship between HO-1 and IL-6 expression suggests a negative feedback loop between these parameters.